PALLIATIVE TREATMENT USING THERMOCHEMOTHERAPY IN PATIENTS WITH LOCALLY ADVANCED REGIONAL METASTASES FROM MALIGNANT HEAD AND NECK TUMORS - M. A. Engibaryan (Опухоли головы и шеи, 2015)
The paper discusses whether palliative treatment using a developed treatment option can be used in patients with regional metastases from malignant head and neck tumors. An analysis of the results of treating 115 patients has established that modified local thermochemotherapy should be performed, which can improve the immediate results of treatment.